The impact of gallium content on degradation, bioactivity, and antibacterial potency of zinc borate bioactive glass - Yazdi, Alireza Rahimnejad; Torkan, Lawrence; Stone, Wendy; Towler, Mark Robert (Wiley, 2017)
Zinc borate glasses with increasing gallium content (0, 2.5, 5, 10, and 15 Wt % Ga) were synthesized and their degradation, bioactivity in simulated body fluid (SBF), and antibacterial properties were investigated. ICP measurements showed that increased gallium content in the glass resulted in increased gallium ion release and decreased release of other ions. Degradability declined with the addition of gallium, indicating the formation of more symmetric BO3 units with three bridging oxygens and asymmetric BO3 units with two bridging oxygens in the glass network as the gallium content in the series increased. The formation of amorphous CaP on the glass surface after 24 h of incubation in SBF was confirmed by SEM, XRD, and FTIR analyses. Finally, antibacterial evaluation of the glasses using the agar disc-diffusion method demonstrated that the addition of gallium increased the antibacterial potency of the glasses against P. aeruginosa (Gram-negative) while decreasing it against S. epidermidis (Gram-positive); considering the ion release trends, this indicates that the gallium ion is responsible for the glasses’ antibacterial behavior against P. aeruginosa while the zinc ion controls the antibacterial activity against S. epidermidis. The statistical significance of the observed trends in the measurements were confirmed by applying the Kruskal-Wallis H Test.